METHYLENE BLUE DYE REMOVAL BY ADSORPTION ONTO NATURAL GAMALAMA VOLCANIC SOIL - Indra Cipta; Nur Jannah Baturante; Khusna Arif Rakhman; Ilham Mauraji; Dini Hadiarti (Jurusan Kimia FMIPA Universitas Lampung, 2025)
The adsorption of Methylene Blue (MB) dye from aqueous solutions using natural adsorbents derived from Gamalama volcanic soil was investigated in this study. The adsorbent materials were characterized by FTIR, X-ray Diffraction (XRD), and Scanning Electron Microscopy (SEM) analyses, confirming the presence of allophane, halloysite, and kaolinite, which exhibit different morphologies and surface properties. Batch adsorption experiments were conducted to evaluate the effects of pH, contact time, and adsorbent mass on the removal efficiency of Methylene Blue. The results demonstrated that Gamalama volcanic soil adsorbents have a high affinity for Methylene Blue, achieving significant removal rates under optimal conditions. The findings suggest that Gamalama volcanic soil is a promising, low-cost, and environmentally friendly adsorbent for treating dye-contaminated wastewater. This study highlights the potential application of natural volcanic soil as an effective adsorbent in environmental remediation. The optimum MB removal was performed by adsorption condition with pH 6, 20 minutes contact time and 30 mg adsorbent.